An Fe60 tetrahedral cage: building nanoscopic molecular assemblies through cyanometallate and alkoxo linkers. Issue 44 (26th August 2016) - Jiménez, J.-R.; Mondal, A.; Chamoreau, L.-M.; Fertey, P.; Tuna, F.; Julve, M.; Bousseksou, A.; Lescouëzec, R.; Lisnard, L.
Abstract : A nanoscopic Fe60 coordination cage (approximately 3 nm) was prepared by the self assembly of a partially blocked tricyanidoferrate(iii ) complex and tris(alkoxo)-based iron(iii ) coordination motifs. Abstract : A nanoscopic Fe60 coordination cage (approximately 3 nm) was prepared by the self assembly of a partially blocked tricyanidoferrate(iii ) complex and tris(alkoxo)-based iron(iii ) coordination motifs. This cage is a rare example of a mixed cyanido/alkoxo-bridged high nuclearity complex and it exemplifies the great potential of this new synthetic route to generate uncommon molecular architectures using cyanometallates as metalloligands versus alkoxo-based polynuclear entities.